A Proof-of-Concept Ecological Momentary Assessment Study of Day-Level Dynamics in Value-Based Decision-Making in Opioid Addiction - Alvarez, Emmanuel E.; Hafezi, Sahar; Bonagura, Darla; Kleiman, Evan M.; Konova, Anna B. (Frontiers in Psychiatry, 2022)
Background. Drug addiction is thought to be characterized by risky and impulsive behavior despite harmful consequences. Whether these aspects of value-based decision-making in people with addiction are stable and trait-like, and the degree to which they vary within-person and are sensitive to changes in psychological state, remains unknown. In this pilot study, we examined the feasibility of distinguishing these state- vs. trait-like components by probing day-level dynamics of risk and time preferences in patients with opioid use disorder (OUD) as they engaged with their natural environment. Methods. Twenty-three individuals with OUD receiving outpatient treatment (40% female; M=45.67 [SD=13.16] years of age) and twenty-one matched healthy community controls (47% female; M=49.67 [SD=14.38] years of age) participated in a 28-day smartphone-based ecological momentary assessment study (1085 person days; M=24.66, SD=5.84). Random prompts administered daily assessed subjects’ psychological state (e.g., mood) and economic preferences for real delayed and risky monetary rewards. Results. Subjects demonstrated dynamic decision-making preferences, with 40-53% of the variation in known risk and ambiguity tolerance, and 67% in discounting, attributable to between-person vs. within-person (day-to-day) differences. We found that changes in psychological state were related to changes in risk preferences, with patients preferring riskier offers on days they reported being in a better mood but no differences between groups in aggregate level behavior. By contrast, temporal discounting was increased overall in patients compared to controls and was unrelated to global mood. The study was well-tolerated, but compliance rates were moderate and lower in patients. Conclusions. Our data support the idea that decision-making preferences in drug addiction exhibit substantial within-person variability and that this variability can be well-captured using remote data collection methods. Preliminary findings suggested that aspects of decision-making related to consideration of risk may be more sensitive to within-person change in global psychological state while those related to consideration of delay to reward, despite also being somewhat variable, stably differ from healthy levels. Identifying the cognitive factors that contribute to opioid use risk in a “real-world” setting may be important for identifying unique, time-sensitive targets for intervention.